Identification of Prohibited Additives in Wines - Anikina Nadezhda; Cherviak Sofia; Gnilomedova Nonna; Ermikhina Marianna (E3S Web of Conferences)
There is no uniform test or “black box method” to establish definitely the authenticity of wine samples. Methods and types of adulteration are constantly being modernized, requesting to improve and develop analytical methods of increasing the efficiency of identification and detection of counterfeits. The goal of the research is to create a system for diagnostics of prohibited process technologies and additives during the wine identification. The studies were carried out in 2016-2023. The objects of research are: wines; model systems obtained by introducing of permitted and prohibited additives. A total of 3.500 samples were examined. Enochemical indicators based on the principles of high-performance and gas-liquid chromatography, potentiometry and colorimetry were identified in the objects. The developed classifying system covers the range of detection of prohibited additives and a number of process technologies: coloring agents of different origin, flavoring agents, organic acids, water, glycerol; sugar- containing substances of non-grape origin, additives of non-grape raw materials. Each element of the system can be used to diagnose several types of counterfeits. The system is open for seeding and spreading. Methods of analysis of classifying indicators are quite simple and available for industrial laboratories of various levels.